EVALUATION OF ROOFTOP SOLAR POWER PLANT (PLTS) WITH ON GRID SYSTEM (CASE STUDY AT SMKN 3 MAKASSAR) - Yusuf Mappeasse, Muhammad; Suhardi Rahman, Edi; Mega Putri Pamuso , Noviola (Jurnal Media Elektrik, 2025)
This research is quantitative descriptive research that aims to determine the results of the evaluation of the PLTS system at SMKN 3 Makassar and also find out what factors affect the feasibility of this renewable energy power plant. Rooftop solar power plant with on-grid system is a system consisting of solar panels installed on the roof of a building that is directly connected to the PLN network, this system makes a building produce its own electricity from sunlight. This research uses documentation and observation methods carried out by direct observation of the PLTS distribution panel and also making observations on the conductor system and cross section. PLTS with polycrystalline type panels usually have an efficiency of around 13% to 16% and based on the results of this study, the lowest efficiency calculation results were obtained on Tuesday, 26 September 2023 operating hours 12.00 with a frequency of 50 Hz, light intensity of 915 W/m2, with a data value of 5773.1 kWh out and 41,450 kWh incoming power with a PLTS efficiency of 13%. Then the highest efficiency calculation occurred on Friday, 06 October 2023 with a frequency of 50 Hz, light intensity of 770 W/m2, with an outgoing data value of 5817.2 kWh and an incoming power of 20,000 kWh with a PLTS efficiency of 29%, therefore it can be concluded that the on-grid rooftop PLTS at SMKN 3 Makassar has a very good ability to convert solar energy into energy.